Kawin Cerai Etnik Sasak (Studi di Kecamatan Suralaga Kabupaten Lombok Timur) - Muzakki Muzakki (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2018)
The results of the study revealed that (1) The factor which encourage marriage and diverce of Sasak Lombok ethnic were (i) Simple process marriage and divorce, (ii) Forcing marriage, (iii) authoritarian husband, (iv) Third party (realives and family), (v) the impact of eloping process, (vi) No emotional attachment,(vii) economy factor, (viii) Domestic violence, (x) Cheating, (xi) Lack of trust to the spouse; (2) The efforts to overcome marriage and divorce of sasak lombok ethnic were (i) Reanalyzed on marriage procession of sasak ethnic, partucularly eloping, the divorce process between both parties must obey the state law especialially talak divorce, (ii) Inimate with the spouse, (iii) Not to bring down one another, (iv) Satisfaction, (v) Handling the conflict with smile, (vi) Thanking, (vii) Talk openly when problem occurs to avoid the hatred, (viii) never bring the past events but learn from the past, (ix) When quarreling watch the tongue, (x) never carried away by the emotion, (xii) Keep confidential on the relationship.Keywords: Marriage And Divorce, Sasak Lombok Ethnic.